2014
DOI: 10.7566/jpsj.83.084709
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Flop Phenomenon of Two-Dimensional Frustrated Antiferromagnets without Anisotropy in Spin Space

Abstract: Motivated by a recent finding of a spin-flop phenomenon in a system without anisotropy in spin space reported in the S = 1/2 Heisenberg antiferromagnet on the square-kagome lattice, we study the S = 1/2 Heisenberg antiferromagnets on two other lattices composed of vertex-sharing triangles by the numerical diagonalization method. One is a novel lattice including a shuriken shape with four teeth; the other is the kagome lattice with √ 3 × √ 3-structure distortion, which includes a shuriken shape with six teeth. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 31 publications
(35 reference statements)
1
32
0
Order By: Relevance
“…Here, note that the present magnetization jump is a phenomenon different from the increase in the magnetization with a step of ÁS z t ¼ 2 as a characteristic of the spin-nematic phase. [20][21][22] In our recent letter, 18) we reported that the magnetization jump with ÁS z t ¼ 2 found at x ¼ 0:85 is attributed to the spin-flop phenomenon in the isotropic spin space, 6,23) through the observation of an abrupt change in the sublattice magnetization as a function of the magnetization. The jump in the magnetization, as in other examples, is known from various numerical studies of spin-1/2 Heisenberg antiferromagnets on some cluster compounds, 24,25) such as dodecahedron cluster, but its mechanism has not yet been discussed.…”
Section: Magnetization and Phase Diagrammentioning
confidence: 99%
“…Here, note that the present magnetization jump is a phenomenon different from the increase in the magnetization with a step of ÁS z t ¼ 2 as a characteristic of the spin-nematic phase. [20][21][22] In our recent letter, 18) we reported that the magnetization jump with ÁS z t ¼ 2 found at x ¼ 0:85 is attributed to the spin-flop phenomenon in the isotropic spin space, 6,23) through the observation of an abrupt change in the sublattice magnetization as a function of the magnetization. The jump in the magnetization, as in other examples, is known from various numerical studies of spin-1/2 Heisenberg antiferromagnets on some cluster compounds, 24,25) such as dodecahedron cluster, but its mechanism has not yet been discussed.…”
Section: Magnetization and Phase Diagrammentioning
confidence: 99%
“…11,[47][48][49] Regarding the existence or the absence of the degeneracy, this behavior is different from the magnetization jump observed in square-kagome-lattice and Cairo-pentagon-lattice antiferromagnets, and so on. [50][51][52][53] Although this behavior occurs irrespective of the value of S, the skip of m at the jump gradually decreases as S is increased. Around m = (9S − 2)/(9S) near the jump for S = 1, 3/2, 2, and 5/2, a region where the gradient of the magnetization process seems small may exist, although the behavior is very faint.…”
mentioning
confidence: 97%
“…In the case of S = 1/2, the m = 1/3 state of several frustrated systems shows an interesting phase transition between the ferrimagnetic state and another state accompanied by a novel spin-flop phenomenon. 27,[50][51][52][53]62 One of the cases is when the kagome lattice is distorted to the √ 3 × √ 3 type. 27 Future studies taking this distortion into account could help us to more clearly estabish the relationship between the nine-site structure pointed out in Ref.…”
mentioning
confidence: 99%
“…5. The size dependence of h 2 is [3][4][5], and the results for J2/J1 = 1.04 are the additional data. The critical fields h1, h2, h3, and h4 are indicated by the red arrows.…”
Section: Square Kagome Lattice and The Exact Diagonalizationmentioning
confidence: 99%